The Function of Leadership and Work Motivation on the Performance of Literature Evangelists within the Organizational Scope of the Seventh-day Adventist Church - Zwarsa Silalahi; Rudolf Weindra Sagala; Alvyn C. Hendriks (PT FORMOSA CENDEKIA GLOBAL, 2023)
Literature is a word that refers to print media or online media whose purpose is as a medium of communication to convey news or general knowledge information to mankind. This ministry is engaged in the dissemination or distribution of spiritual print media in the form of tracts, magazines, health books and spiritual books with the sole aim of spreading the everlasting gospel throughout the world. To distribute such books need evangelist literature. Literature Evangelists are the ones who are at the forefront of this evangelistic ministry because they are the ones directly involved in interacting with the community, so they need to have a spirit of good performance and full of submission to God. However, the reality is that the Literature Evangelist Service has not been running effectively and efficiently. This research uses qualitative methods by analyzing and concluding the data obtained related to research. The purpose of this study was to determine the influence of leaders in improving the performance of literature evangelists and literature evangelists who have the right motivation to be involved in literature evangelism services. In doing a job a person needs one or more motivations that can be the spirit or basis for doing a job. Strong motivation will encourage someone to be able to do his job well. In this case the leader has the responsibility to provide motivation in improving the performance of literature evangelists.